Potawatomi materials, Anthony F. C. Wallace Papers - Wallace, Anthony F. C., 1923-2015; Quimby, George I. (George Irving), 1913-2003; Kane, Michal Lowenfels; Stewart, Omer Call, 1908-1991 (1950)
The Anthony F. C. Wallace Papers are a vast collection of materials relating to Wallace's work at the intersection of anthropology, psychology, and history. Though further research might yield more results, approximately 25 items directly pertaining to the Potawatomi have been identified. The majority of these materials are located in Series IX. Indian Claims, and relate to Wallace's work as a researcher and expert witness on behalf of Native American land claims. Research materials include notes on Potawatomi locations, political organization, and treaty signers by Wallace's assistant Michal Kane, two folders of Wallace's notes, a folder containing an ethnohistorical research paper by anthropologist and museum curator George Quimby, and "Regulations Books" containing reports on tribal history and treaties. Court materials include several dockets, trial memoranda, court findings and briefs, and hearing transcripts. There is also an essay by Wallace titled "Potawatomi Political System and Tribal Membership" and a folder relating to the financial aspect of Wallace's service. See also the Omer Call Stewart file in Series I. Correspondence and the research notecards in Series III. Notecards. See the finding aid for a detailed discussion of Wallace's long and varied career, and for an itemized list of the collection's contents.